Pengaruh Non Performing Loan (NPL) Dan Return On Asset (ROA) Terhadap Return Saham Pada Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia Periode 2017-2019 - Zein Ghozali; Sri Sutandi; Masnoni; Nelly; Sisilia Intan Barokah (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2021)
This study aims to examine the effect of non-performing loans (NPL) and return on assets (ROA) on stock returns in banking companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2019 period. By using 2 indicators, namely Non Performing Loans (NPL) and Return On Assets (ROA) as independent variables, and Stock Returns as the dependent variable. This study uses corporate financial statement data taken from www.idx.co.id.The population of this study were banking companies listed on the Indonesia Stock Exchange (IDX) for the 2017-2019 period with a sample of 12 companies so that the total n (data) studied for 3 years was 36. The sample was drawn using purposive sampling using multiple linear regression analysis of the SPSS for Windows Version 22 program. The results of this study obtained an R Square (R2) value of 0.185 (18.5%) which means stock returns can be explained by NPL and ROA, the remaining 81.5% influenced by other factors not included in this study. Fcount value 4.975 > Ftable value of 4.13 with a significant level of 0.013 <0.05, which means that the NPL and ROA variables have a significant effect on stock returns. Results the t test for the NPL variable is 0.616 with a significance level of 0.542 > 0.05 which means that NPL has no effect on stock returns and the ROA variable test results are 3.144 with a significant level of 0.004 <0.05 which means ROA has an effect on stock returns.